Distinctive capabilities and strategic thrusts of Malaysia’s institutions of higher learning - Abu Bakar, Abdul Rahim; Hashim, Fariza; Ahmad, Hartini; Md Isa, Filzah; Dzakiria, Hisham (Canadian Center of Science and Education, 2009)
The hostile business environment in Malaysian private higher education institutions (PHEIs) has proved to be fatal to numerous institutions.While there are success stories, the issue looms as what differentiates the performers and the non performers. As such, this study was conducted to understand why some PHEIs perform better than others; and whether the differences in performance are due to the choice of strategy.Finally, this study explores whether the organisational distinctive capabilities influence towards the institution choice of strategy. Based from a sample of 97 PHEIs, the study depicts that differentiation strategy was significantly link to performance with a spectrum of organisational capabilities influencing the institution’s choice of strategy.